Analisis Usability pada Human Capital Management System PT. XYZ menggunakan WEBUSE Model - Alia Mutia Mayanda; Agnes Sondita Payani; Adenia Adiresta; Imairi Eitiveni (Journal of Applied Computer Science and Technology, 2023)
Human Capital Management System (HCMS) has become a necessity for organizations to perform administrative personnel services. PT XYZ started implementing HCMS in 2019 as an online self-service for personnel administration, which was previously done manually. During this transition phase, not all employees understand how to use the HCMS system due to its confusing interface. As a result, many employees still prefer assistance from the HR/IT team to make changes to their data rather than doing it themselves. This research was conducted to analyze the usability of the HCMS system using the WEBUSE method. There are four categories used: Content, Organization, and Readability (COR); Navigation and Links (NAL); User Interface Design (UID); and Performance and Effectiveness (PAE). Each category serves as a basis for measuring usability. Data was collected through questionnaires and interviews with respondents to obtain values and levels of WEBUSE usability based on user satisfaction aspects In the case study of this research, it was obtained from the results of the questionnaire distributed as many as 13 respondents stated that in general, the usability of the HCMS system was at the Good level. This research provides recommendations for improving the self-service HCMS based on the needs or experiences of employees using the system. Also contributes to the scientific study of UI/UX and provides an ideal overview practitioner in developing an HCMS system.